Blockchain in Capital Markets: A Revolution of the Trading System in Stock Exchange - Dian Kusuma Wardhani; Tjiptohadi Sawarjuwono; Sasongko Budisusetyo (The Indonesian Accounting Review, 2022)
This study aims to explore the benefits of implementing blockchain technology as a basis for stock trading in Indonesia to improve the corporate governance of issuers. Two main factors that trigger the emergence of agency problems in corporate gov-ernance in traditional stock exchanges are differences in interests between principals and agents and the complexity of the investment chain. This research is a documen-tary research where the researchers search for references in the form of previous research using the keyword “blockchain” in the “publish” or “perish” application. Next, the researchers organize, make a written summary, and interpret the findings obtained based on the the researchers’ thoughtd. Based on the interpretation of pre-vious research, compared to traditional stock trading systems, blockchain technology has several advantages, such as high information transparency, improved stock liquidity, high monitoring by various parties, and the availability of information in real-time, thereby creating better corporate governance. The implementation of blockchain technology can reduce information asymmetry in the relationship between principal and agent, which in turn can improve the quality of corporate governance due to transparency, accountability, and high trust between all parties involved in this blockchain technology network.